Semantyka upamiętniania w języku polskim, niemieckim i hiszpańskim - Krysiak (Dobkiewicz), Magdalena (Studia Europaea Gnesnensia, 2011)
In the article, I attempt a slightly closer insight into the meaning of the word “com-memorate” in Polish, German and Spanish in the hope of finding its semantic invariant. The principal aim is to answer the question which activities the verb commemorate is made to serve by the members of the three language communities when formulating utterances concerning the handing down of the memory to posterity.